Spatial Hearing Difficulties in Reaching Space in Bilateral Cochlear Implant Children Improve With Head Movements. Issue 1 (January 2022) - Coudert, Aurélie; Gaveau, Valérie; Gatel, Julie; Verdelet, Grégoire; Salemme, Romeo; Farne, Alessandro; Pavani, Francesco; Truy, Eric
Abstract : Objectives: The aim of this study was to assess three-dimensional (3D) spatial hearing abilities in reaching space of children and adolescents fitted with bilateral cochlear implants (BCI). The study also investigated the impact of spontaneous head movements on sound localization abilities. Design: BCI children (N = 18, aged between 8 and 17) and age-matched normal-hearing (NH) controls (N = 18) took part in the study. Tests were performed using immersive virtual reality equipment that allowed control over visual information and initial eye position, as well as real-time 3D motion tracking of head and hand position with subcentimeter accuracy. The experiment exploited these technical features to achieve trial-by-trial exact positioning in head-centered coordinates of a single loudspeaker used for real, near-field sound delivery, which was reproducible across trials and participants. Using this novel approach, broadband sounds were delivered at different azimuths within the participants' arm length, in front and back space, at two different distances from their heads. Continuous head-monitoring allowed us to compare two listening conditions: "head immobile" (no head movements allowed) and "head moving" (spontaneous head movements allowed). Sound localization performance was assessed by computing the mean 3D error (i.e. the difference in space between the X-Y-Z position of the loudspeaker and the participant's final hand position used to indicate the localization of the sound's source), as well as the percentage of front–back and left–right confusions in azimuth, and the discriminability between two nearby distances. Several clinical factors (i.e. age at test, interimplant interval, and duration of binaural experience) were also correlated with the mean 3D error. Finally, the Speech Spatial and Qualities of Hearing Scale was administered to BCI participants and their parents. Results: Although BCI participants distinguished well between left and right sound sources, near-field spatial hearing remained challenging, particularly under the " head immobile" condition. Without visual priors of the sound position, response accuracy was lower than that of their NH peers, as evidenced by the mean 3D error (BCI: 55 cm, NH: 24 cm, p = 0.008). The BCI group mainly pointed along the interaural axis, corresponding to the position of their CI microphones. This led to important front–back confusions (44.6%). Distance discrimination also remained challenging for BCI users, mostly due to sound compression applied by their processor. Notably, BCI users benefitted from head movements under the "head moving" condition, with a significant decrease of the 3D error when pointing to front targets ( p < 0.001). Interimplant interval was correlated with 3D error ( p < 0.001), whereas no correlation with self-assessment of spatial hearing difficulties emerged ( p = 0.9). Conclusions: In reaching space, BCI children and adolescents are able to extract enough auditory cues to discriminate sound side. However, without any visual cues or spontaneous head movements during sound emission, their localization abilities are substantially impaired for front–back and distance discrimination. Exploring the environment with head movements was a valuable strategy for improving sound localization within individuals with different clinical backgrounds. These novel findings could prompt new perspectives to better understand sound localization maturation in BCI children, and more broadly in patients with hearing loss. Abstract : Supplemental Digital Content is available in the text.